The exposure of media frames among Malaysian bloggers pre and post 13th General Election - Muhammad Hakimi Tew Abdullah; Abdul Latiff Ahmad; Chang, Peng Kee (Penerbit Universiti Kebangsaan Malaysia, 2016)
Blog began to attract people in Malaysia in 1998 when bloggers actively wrote about political matters and current issues. Blogs have then become an influential medium of news reporting after the mass community rejects mainstream media which often shows favoritism to the government party. This paper examines how a generic frames used by the bloggers in Malaysia pre and post 13th General Election (GE). A comparison on two groups of blog is made which involved Pro- Barisan Nasional (BN) and Pro- Pakatan Rakyat (PR) to see the differences in the use of frames by the bloggers. Five generic frames with 20 attributes statement by Semetko & Valkenburg has been adapted in this study. Quantitative content analysis approach was used and the results showed that conflict frame and responsibility frame are at a relatively high level use while the human interest frame, morality frame and economic consequences frame are at the low level of use. However, there are some differences in terms of the use of frames by both groups of blogger even at different political views. The results of the study clearly show that both groups of bloggers have emphasized more conflict frames in all the issues debated.